2010
DOI: 10.1007/s00484-010-0325-1
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of central versus sweat gland mechanisms to the seasonal change of sweating function in young sedentary males and females

Abstract: In summer and winter, young, sedentary male (N = 5) and female (N = 7) subjects were exposed to heat in a climate chamber in which ambient temperature (Ta) was raised continuously from 30 to 42°C at a rate of 0.1°C min(-1) at a relative humidity of 40%. Sweat rates (SR) were measured continuously on forearm, chest and forehead together with tympanic temperature (Tty), mean skin temperature (⁻Ts) and mean body temperature ⁻Tb. The rate of sweat expulsions (Fsw) was obtained as an indicator of central sudomotor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 39 publications
2
27
0
Order By: Relevance
“…These studies reported a greater sweat gland expulsion frequency, a proposed marker of central sudomotor activity, following heat acclimation (Ogawa & Sugenoya, 1993) and seasonal acclimatization (Taniguchi et al . 2011). By contrast, we determined how heat acclimation modulates skin sympathetic nerve activity, comprising the efferent neural signal that activates sweating and cutaneous vasodilatation (Hagbarth et al .…”
Section: Discussionmentioning
confidence: 99%
“…These studies reported a greater sweat gland expulsion frequency, a proposed marker of central sudomotor activity, following heat acclimation (Ogawa & Sugenoya, 1993) and seasonal acclimatization (Taniguchi et al . 2011). By contrast, we determined how heat acclimation modulates skin sympathetic nerve activity, comprising the efferent neural signal that activates sweating and cutaneous vasodilatation (Hagbarth et al .…”
Section: Discussionmentioning
confidence: 99%
“…These effects could result in interpretation errors of sEMG findings in human performance studies, depending on the nature of the study and onset of signal deterioration. Furthermore, the rate of sweating changes over time, being dependent on: passive heating (Taniguchi et al, 2011), exercise (Flouris and Cheung, 2010;Smith and Havenith, 2011) and influenced by individual differences in sweat rates (Cotter et al, 1995) as well as time of day (Aoki et al, 2002), seasons (Aoki et al, 2002), gender (Kenny and Jay, 2007;Taniguchi et al, 2011) and age (Dufour and Candas, 2007). This makes sweating a difficult factor to control in experimental studies, especially those carried out in the workplace where the environmental conditions cannot be controlled and protective clothing is often required.…”
Section: Introductionmentioning
confidence: 97%
“…Little is known regarding the amount of sweat needed to accumulate before signal fidelity deteriorates. Thresholds for sweating have been reported as low as 36°C body temperature with passive heating (Taniguchi et al, 2011) and 10 min of graded exercise reaching 20% VO 2max (Takano et al, 1996) indicating that sweating is a factor in most workplace studies that are investigating physical work demands. Maximal sweat rates have been shown to occur along the length of the spine and across the mid back (Havenith et al, 2008;Smith and Havenith, 2011) at rates exceeding 2000 mg m À2 h À1 with high intensity exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, age and sex are major elements determining how humans modulate homeostasis between the environment and body temperature. Differences in sweat gland function are observed between male and female subjects . Older women show a lower whole‐body sweating rate than young women because aging attenuates the sweat gland response and mechanism controlled by a central sudomotor mechanism .…”
Section: Introductionmentioning
confidence: 99%
“…Efferent sweat fibres originate in the preoptic area and anterior hypothalamus and descend to the post‐ganglionic sympathetic plexus (sudomotor neurons) through the ipsilateral brain stem and medulla . The sweat glands generate a sweat response to central sudomotor nerve activity . In addition, peripheral conditions (local skin temperature and blood flow) can modulate the sweating response …”
Section: Introductionmentioning
confidence: 99%